Premier Carwash Centre / Noorismy Khairi … [et al.] - Khairi, Noorismy; Mokhtar, Norlian; Abdul Moin, Norfadilah; Malik, Iza Mazlinda; Samsudin, Natisya (2000)
Premier Carwash Centre is a business venture that involved five members, form as a partnership. We will start our business at 1 January 2002. Our goals are to provide a service that fulfils the customer satisfaction. Our business target is at Melaka city because of its strategic location. We also provide a service to near place such as Bachang, Tengkera and Bukit China. We not only provide a cleaning service but including polishing and car vacuuming. For that reason, it is our responsibility to provide skilled and experienced employees in this field. With the experienced and skilled employees, all the problems will be resolve. We hope that our business will develop and as an example to other people to join venture.